2022
DOI: 10.1101/2022.06.20.496737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chrna5 and lynx prototoxins identify acetylcholine super-responder subplate neurons

Abstract: Attention depends on cholinergic excitation of prefrontal neurons. Knockout/knockdown studies indicate nicotinic alpha5 subunits encoded by Chrna5 are required for this response, but their native cellular roles and molecular interactions are unknown. Here, we probe endogenous cholinergic regulation of prefrontal Chrna5-expressing neurons (Chrna5+) using compound transgenic mice. Chrna5+ neurons show high sensitivity to acetylcholine, with a subpopulation clearly different from nearby, well-examined Syt6+ cells… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…In addition, a recent study identified excitatory subplate neurons termed 'ACh super-responders' due to their pronounced ACh-induced depolarisations (Venkatesan et al, 2022), a feature resembling the L6b CT PCs described here. Layer 6b is considered to be a remnant of the subplate (Hoerder-Suabedissen and Molnar, 2012; Marx et al, 2017;Reep, 2000;Torres-Reveron and Friedlander, 2007), which suggests that L6b excitatory neurons retain the high ACh responsiveness akin to the 'ACh super-responder' subplate neurons during early postnatal development.…”
Section: Cholinergic Neuromodulation Of Foxp2+ and Foxp2-excitatory N...supporting
confidence: 55%
“…In addition, a recent study identified excitatory subplate neurons termed 'ACh super-responders' due to their pronounced ACh-induced depolarisations (Venkatesan et al, 2022), a feature resembling the L6b CT PCs described here. Layer 6b is considered to be a remnant of the subplate (Hoerder-Suabedissen and Molnar, 2012; Marx et al, 2017;Reep, 2000;Torres-Reveron and Friedlander, 2007), which suggests that L6b excitatory neurons retain the high ACh responsiveness akin to the 'ACh super-responder' subplate neurons during early postnatal development.…”
Section: Cholinergic Neuromodulation Of Foxp2+ and Foxp2-excitatory N...supporting
confidence: 55%
“…The atropine-sensitivity and postsynaptic PKC-dependence of its nicotinic receptor upregulation points to an excitatory muscarinic mechanism, but xanomeline has also been shown to inhibit M4 receptors [100,101] and could potentially disinhibit glutamate release. Our data implicate the involvement of PKC, typically activated by Gαq-signaling, but this signaling also triggers activation of PLC [102] and may regulate GPI-anchored lynx family proteins [103] that also modulate nicotinic receptors [104,105] directly [106108] or indirectly [107,109]. We find an improvement in apparent nicotinic receptor availability, however, the question of the density and localization of nicotinic receptors prior to-and after treatment remains outstanding.…”
Section: Discussionmentioning
confidence: 85%